FAKTOR RISIKO KEJADIAN FILARIASIS DI KECAMATAN TIRTO KABUPATEN PEKALONGAN - Kristian Yudhianto; Lintang Dian Saraswati; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Lymphatic filariasis is a public health problem in the District of Tirto, Pekalongan Regency with 18 filariasis clinical cases in 2015 and still poddible transmission. Risk factors need to know as a basis for determining the preventive efforts. The purpose of this study to identify risk factors for incicidence of filariasis in the District of Tirto, Pekalongan Regency. Research using a cross sectional study design. Groups of positive filariasis are all positive population filariasis detected based on ICT examination results while the negative filariasis group are all negative filariasis based on ICT examination in 2015. The instrument was a questionnaire and the observation sheet. Data analysis using Chi Square. Result showed that the variables proved to be a risk factor is the prevention knowledge of filariasis OR 0,202 (95%CI 0,065-0,627), the filariasis prevention attitude OR 0,209 (95%CI 0,065-0,675), the habit of using mosquito net OR 0,271 (95%CI 0,088-0,839) and habit of hanging clothes OR 6,308 (95%CI 1,974-20,155). While the variable that is not a risk factor is sex, age, education, occupation, body mass index, resident status, wire netting, presenced of bushes, exsistenced puddles and conditions ofa waste water sewer. Thus prevention of filariasis that could be done in the District of Tirto, Pekalongan Regency is to give information about the behavior at risk factor of filariasis occurrence, especiallu about the use of mosquito net and hanging clothes.